La Storia è diventata un luogo della memoria? - Hartog, François (Studi Politici, 2023)
The article analyses the XX century revolutionary transition that, on the final stages of both colonialism and the Second World War, led to a vision of History no longer as a paradigm under which man could gain a deeper understanding of his own path looking it through the lens of the past, but as a growing acceleration that looses itself in an endless progress. For now, scholars can only follow this spiral, venturing out in search of a plural History, able to subsume unto itself all the possible futures that may come. Therefore, waiting for the wider concept of Histories to take over from its singular, monolithic version, academics try to make in fit into a more general definition, such as the one, more and more popular, of Global History.